Assessment of the level of knowledge of patients from selected Warsaw hospitals about Crohn’s disease - Turek, Karolina; Gotlib, Joanna (Medical Studies/Studia Medyczne, 2013)
Introduction: Crohn’s disease constitutes one of the most serious diagnostic-therapeutic problems of contemporary gastroenterology and appropriate lifestyle may prevent symptoms of this disease. Aim of the research: To assess the level of patient knowledge of Crohn’s disease. Material and methods: The study enrolled 100 patients from three Warsaw hospitals (53 women). Mean age of the study population was 34.6 years (min. 18, max. 60; SD = 5.690). The voluntary and anonymous questionnaire study used a questionnaire developed by the authors (32 questions). Statistical analysis of the study results was carried out in the StatSoft Statistica 10.0 program, using the Mann-Whitney U test. The significance level was established at p < 0.05. Results : The study group of patients had basic knowledge of Crohn’s disease. A majority of the study participants (over 60%) knew the key factors responsible for the development of non-specific inflammatory bowel disease, 64% of them knew the effects of immunosuppressive therapy, and 77% of the patients correctly indicated the group of drugs used in the therapy; however, detailed knowledge of the disease significant for further treatment and its influence on the quality of life was insufficient and required supplementation. Differences among women and men were statistically insignificant (p = NS). Conclusions : Studies on patient knowledge of Crohn’s disease are rarely published in Polish and world scientific literature and therefore there is a need for continuation of studies. Detailed knowledge of patients about Crohn’s disease was insufficient. Therefore, information campaigns and actions as well as continuous education of patients performed by members of interdisciplinary therapeutic teams are justified. The level of knowledge of Crohn’s disease is not gender-related. The study results may be used in practice for development of educational programmes for patients with this disease.